Safety and Immunogenicity of an Inactivated COVID-19 Vaccine, WIBP-CorV, in Healthy Children: Interim Analysis of a Randomized, Double-Blind, Controlled, Phase 1/2 Trial - Xia, Shengli; Duan, Kai; Zhang, Yuntao; Zeng, Xiaoqing; Zhao, Dongyang; Zhang, Huajun; Xie, Zhiqiang; Li, Xinguo; Peng, Cheng; Zhang, Wei; Yang, Yunkai; Chen, Wei; et al. (Frontiers in Immunology, 2022)
Safe and effective vaccines against SARS-CoV-2 for children are urgently needed. Here we aimed to assess the safety and immunogenicity of an inactivated COVID-19 vaccine candidate, WIBP-CorV, in participants aged 3-17 years. A randomized, double-blind, placebo-controlled, phase 1/2 clinical trial was conducted in Henan Province, China, in healthy children aged 3-17 years. 240 participants in phase 1 trial and 576 participants in phase 2 trial were randomly assigned to vaccine or control with an age de-escalation in three cohorts (3-5, 6-12 and 13-17 years) and dose-escalation in three groups (2.5, 5.0 and 10.0μg/dose), and received 3 intramuscular injections at day 0, 28, and 56. WIBP-CorV showed a promising safety profile with approximately 17% adverse reactions within 30 days after injection and no grade 3 or worse adverse events. The most common adverse reaction was injection site pain, followed by fever, which were mild and self-limiting. The geometric mean titers of neutralizing antibody ranged from 102.2 to 1065.5 in vaccinated participants at 28 days after the third vaccination, and maintained at a range of 14.3 to 218.2 at day 180 after the third vaccination. WIBP-CorV elicited significantly higher titers of neutralizing antibody in the cohort aged 3-5 years than the other two cohorts. There were no detectable antibody responses in all alum-only groups. Taken together, our data demonstrate that WIBP-CorV is safe and well tolerated at all tested doses in participants aged 3-17 years, and elicited robust humoral responses against SARS-CoV-2 lasted for at least 6 months after the third vaccination. This study is ongoing and is registered with www.chictr.org.cn, ChiCTR2000031809.